Konseling Indigenous Menggali Nilai-nilai Kearifan Lokal Tradisi Nazar ke Puyang Pada Masyarakat - Karlin, Rezaning Destri; Kusnadi, Kusnadi; Cung, Vinny (Journal of Society Counseling, 2024)
This research is entitled "Indigenous counseling explores the values of local wisdom of the Nazar ke Puyang tradition in the community of Sumber Rahayu Village, Rambang District, Muara Enim Regency" nazar is a promise to Allah SWT when our wish has been achieved, this is different from the Nazar tradition in Sumber Rahayu Village who asked for and paid vows to Puyang grave. This research aims to find out the description of the Nazar ke Puyang tradition or people's belief in the spirits of their ancestral ancestors, whether this tradition is still being carried out or has begun to be abandoned and wants to know the process and origins of this tradition. The approach used in this research is a descriptive qualitative approach with field research or collecting data directly in the field according to the facts that occur. The data collection techniques used are observation, interviews and documentation as well as presenting this data in table form so that it is easy to understand. Data analysis techniques include data presentation, data reduction and conclusions. The results of this research are that there are still people who make vows to Puyang, especially older natives, but the aim is not to become Musrikan, just to preserve traditional customs that have existed since the time of our ancestors, which have been passed down from generation to generation. next. The indigenous value contained in this tradition is the authenticity of this tradition which has existed since ancient times. This Indigeneous Counseling involves residents who make vows and the local village traditional heads.